2010
DOI: 10.1016/j.jjcc.2009.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Catheter ablation of atrial fibrillation guided by complex fractionated atrial electrogram mapping of atrial fibrillation substrate

Abstract: Cardiologists and physicians have witnessed a significant change in the management of atrial fibrillation (AF): antiarrhythmic agents are no longer considered more effective than just merely using compounds that control ventricular response of the arrhythmia with anticoagulation in high-risk patients. Catheter ablation has grown into wider acceptance as an important therapeutic modality in treating tachyarrhythmias. And over the past decade, several studies have clearly established that catheter ablation of at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
99
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(104 citation statements)
references
References 35 publications
5
99
0
Order By: Relevance
“…They showed that AF was terminated in over 85% of the patients, and reported that after CFAE ablation, 93% of the patients with paroxysmal AF, 87% of the patients with persistent AF and 78% of the patients with longstanding persistent AF were arrhythmiafree including 11% of the patients taking antiarrhythmic drugs. 34) However, their results were not fully reproduced by others. Oral et al 35) performed ablation of CFAE in patients with chronic AF.…”
Section: Ablation Of Cfaementioning
confidence: 83%
See 2 more Smart Citations
“…They showed that AF was terminated in over 85% of the patients, and reported that after CFAE ablation, 93% of the patients with paroxysmal AF, 87% of the patients with persistent AF and 78% of the patients with longstanding persistent AF were arrhythmiafree including 11% of the patients taking antiarrhythmic drugs. 34) However, their results were not fully reproduced by others. Oral et al 35) performed ablation of CFAE in patients with chronic AF.…”
Section: Ablation Of Cfaementioning
confidence: 83%
“…They demonstrated that ablation of CFAE resulted in termination of AF in 95% of the patients; however, 28% required concomitant ibutilide treatment. 34) We used antiarrhythmic drugs before CFAE ablation in 60 patients, including 38 with longstanding persistent AF and 22 with persistent AF who underwent box isolation. After box isolation, CFAE maps were created before and after infusion of a pure Na þ blocker, pilsicainide (1 mg/kg), in 30 patients or a pure I Kr blocker, nifekalant (0.3 mg/kg), in 30 patients.…”
Section: Hybrid Approach Of Combining Box Isolation With Cfae Ablationmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, there is a close relationship between autonomic ganglionated plexi activity and CFAE. 8 Nademanee et al 37 showed that AF was terminated in over 85% of patients, and reported that after CFAE ablation, 93% of the patients with paroxysmal AF, 87% of patients with persistent AF and 78% of patients with longstanding persistent AF were arrhythmia-free, including 11% of the patients taking antiarrhythmic drugs. However, their results were not fully reproduced by others.…”
Section: Ablation Of Cfaementioning
confidence: 99%
“…They demonstrated that ablation of CFAE resulted in termination of AF in 95% of patients; however, 28% required concomitant ibutilide treatment. 37 …”
Section: Ablation Of Cfaementioning
confidence: 99%